2011
DOI: 10.2108/zsj.28.134
|View full text |Cite
|
Sign up to set email alerts
|

Cribrimorph and OtherCauloramphusSpecies (Bryozoa: Cheilostomata) from the Northwestern Pacific

Abstract: We provide original descriptions for nine new species in the cheilostome bryozoan genus Cauloramphus (C. gracilis, C. ordinarius, C. amphidisjunctus, C. cheliferoides, C. oshurkovi, C. infensus, C. parvus, C. peltatus, and C. ascofer) and a redescription of C. disjunctus Canu and Bassler, 1929. We delineate a group of eight species, here termed the 'C. disjunctus clade,' that have the opesial spine joints calcified to a greater or lesser extent in mature zooids; most also have paired, hypertrophied avicularia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Indeed, the Indonesian Throughflow may be the best analogy we have today for the processes existing for several millions of years prior to the final emergence of the Isthmus of Panama. Recent studies also suggest similar local isolations and subsequent allopatric speciation of other cheilostome bryozoans in the Aluetian straits (Dick 2008;Dick et al 2011).…”
Section: Discussionmentioning
confidence: 74%
“…Indeed, the Indonesian Throughflow may be the best analogy we have today for the processes existing for several millions of years prior to the final emergence of the Isthmus of Panama. Recent studies also suggest similar local isolations and subsequent allopatric speciation of other cheilostome bryozoans in the Aluetian straits (Dick 2008;Dick et al 2011).…”
Section: Discussionmentioning
confidence: 74%
“…Although there was evidence that both the costal shield and ascus evolved independently several times in cheilostomes (Voigt 1991;Gordon 2000), the discovery of the parallel Neogene origin of these structures in closely related species within a single welldefined genus, Cauloramphus, in the large anascan family Calloporidae, forced a reassessment of the significance and pervasiveness of convergence in these structures (Dick et al 2009(Dick et al , 2011. Several Cauloramphus species comprise a transition series, from a stereotypical anascan with an exposed frontal membrane surrounded by jointed opesial spines (Fig.…”
Section: Zooid Costal Shieldsmentioning
confidence: 99%
“…a C. ordinariusDick et al, 2011. b C. cheliferoides Dick et al, 2011. c C. peltatus Dick et al, 2011. d C. ascofer Dick et al, 2011 …”
mentioning
confidence: 99%
“…HincKs (1885) showed that separation of zooids in other cheilostomes is not necessarily a generic character as it occurs in species belonging to several different genera. A good example is seen in the genus Cauloramphus in which tubules are lacking in the majority of species but are present in C. disjunctus canu & BasslEr, 1929and C. amphidisjunctus DicK, Mawatari, sannEr & griscHEnKo, 2011(DicK et al 2011.…”
Section: Taxonomymentioning
confidence: 99%